2022
DOI: 10.1002/csr.2414
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility, family involvement, and stock price crash risk

Abstract: This study responds to the call in Vazquez's (2018) by providing more empirical evidence on ethical issues in family business. Drawing from the agency theory, we provide new evidence about the "CSRstock price crash risk" nexus by examining the moderating effect of family involvement. With a focus on the Chinese capital market, we find that corporate social responsibility (CSR) negatively affects stock price crash risk. Such negative correlation is stronger for family firms as compared with nonfamily firms. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 163 publications
0
0
0
Order By: Relevance
“…Another study using ESG disclosure, Silva (2022) analyzed ESG disclosure with crash risk in global companies from 2007-2019, concluding that ESG disclosure weakens future firm-specific crash risk. The same results were shown by (Bae et al, 2021;Hua Fan, and Michalski, 2020;Yang et al, 2023) which showed that ESG disclosure was able to mitigate the company's future stock price crash risk.…”
Section: Esg Disclosure Business Strategy and Stock Price Crash Risksupporting
confidence: 67%
“…Another study using ESG disclosure, Silva (2022) analyzed ESG disclosure with crash risk in global companies from 2007-2019, concluding that ESG disclosure weakens future firm-specific crash risk. The same results were shown by (Bae et al, 2021;Hua Fan, and Michalski, 2020;Yang et al, 2023) which showed that ESG disclosure was able to mitigate the company's future stock price crash risk.…”
Section: Esg Disclosure Business Strategy and Stock Price Crash Risksupporting
confidence: 67%
“…Xu et al ., 2013; He et al ., 2019; Kim et al ., 2019; Yang et al. , 2023a, b). The foundation of literature on stock price crash risk revolves around the concept of managerial behaviour characterised by the hoarding of negative news, driven by factors such as informational opacity and agency conflicts (Jin and Myers, 2006; Hutton et al ., 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Referring to existing literature [34], according to the idea of "selecting winners", the government is more willing to select truly excellent enterprises, subsidize projects with high success rates, and minimize market distortion. Additionally, scholars have also pointed out that fulfilling corporate social responsibility is beneficial for improving stakeholder relationships and gaining more trust [35]. However, in reality, enterprises may engage in negative events that violate their original intentions of operation and harm social benefits driven by interests [36].…”
Section: Esg Performance and Government Subsidiesmentioning
confidence: 99%